Removing imidacloprid, bisphenol-S and azithromycin by ferrate (Fe(VI)): efficiency, oxidation products, toxicity and kinetics - Shaoqing Zhang; Jia-Qian Jiang; Michael Petri (Environmental Challenges, 2022)
Emerging micro-pollutants (EMPs) have potential threats to human health and eco-environment. It is necessary to seek alternative treatment technologies when the existing processes have limitations to treat EMPs. This paper aimed to investigate the use of ferrate (Fe(VI)) to treat imidacloprid (IMP), bisphenol-S (BS) and azithromycin (AZM) by assessing the toxicity of the EPMs before and after Fe(VI) treatment, generating reaction kinetic rate constants and proposing degradation pathways and oxidation products. BS was readily removed at a lower Fe(VI) dose of 0.009 mM, while both IMP and AZM were not be effectively degraded at such a low Fe(VI) dose. The resulting toxicity of BS was reduced after Fe(VI) treatment, whereas that of IMP and AZM treated by Fe(VI) increased; this is due to changes in structure and property of EMPs and the formation of oxidation products (OPs), which induced either low or high toxicity. The pseudo-first-order reaction rates of IMP, BS, and AZM with Fe(VI) were derived as 0.071, 0.148, and 0.076 s−1 respectively, which are consistent with the trend of the EMPs’ removing by Fe(VI).